Epidemiological study on animal bite cases referred to Haji Daii health Center in Kermanshah province, Iran during 2013-2017 - Maryam Janatolmakan; Mojtaba Delpak; Alireza Abdi; Sabah Mohamadi; Bahare Andayeshgar; Alireza Khatony (BMC, 2020)
Abstract Background Over thousands of animal bite cases are reported annually worldwide and in Iran placing a large financial burden on the health and economy. The aim of this study was to evaluate the epidemiology of animal bite cases in Kermanshah, Iran through 2013-2017. Methods In this cross-sectional study, 5618 animal bite cases in Kermanshah from 2013 to 2017 were studied. Data were analyzed using descriptive and inferential statistics. Results In the study period, 5618 animal bite cases were found. The prevalence of animal bites was estimated between 42.55-45.66 per100000 populations during 2013-2017. An increasing significant trend was found for prevalence of animal bites (Average annual percent change [AAPC] + 4.9, P-trend< 0.001) over a 5-years' time period. The mean age of the subjects was 32.7 ± 18.3 years. Of the studied subjects 76.3% were male, and 34% had non-governmental jobs. Dogs were found as the cause of animal bites in 72% of the cases. Of the studied cases, 82% had received rabies vaccination for three times. Conclusion The results showed an increasing significant trend for animal bites in Kermanshah. Development of interventional programs, such as limiting stray dogs, vaccination of dogs and raising public awareness are essential.